CALCULATION OF EXPECTATION VALUES OF MOLECULAR-SYSTEMS USING DIFFUSION MONTE-CARLO IN CONJUNCTION WITH THE FINITE-FIELD METHOD - Sandler, P; Buch, V; Clary, D (1994)
A scheme employing the finite field method is proposed for extracting expectation values of molecular properties from diffusion Monte Carlo calculations. The method enables calculation of expectation values of nonlocal operators, such as kinetic energies of molecular components of the system. The method is demonstrated for the H2O⋯N2 cluster. © 1994 American Institute of Physics.